War Atrocities Against Civilian Population
Appears to be the first entry into Vocin, Zvecevo & Cetekovac villages after "ethnic cleansing". Many dead civilians lay where they fell; in the grass, near the road. Destruction of civilian property. Livestock heard and seen still roaming.